2021
DOI: 10.1111/ejn.15099
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the laterality of motor unit behavior in female patients with parkinson's disease using high‐density surface electromyography

Abstract: Patients with Parkinson's disease (PD) have greater laterality of muscle contraction properties than other people with parkinsonism diseases. However, few studies have reported the laterality of MU activation properties of the lower extremity muscles in patients with PD. The aim of the present study was to identify the laterality of MU behavior in PD patients using high-density surface electromyography (HD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…The more-affected side showed a lower knee extensor torque, recruitment threshold, and SBR Bolt , and a higher CV of the mean MU firing rate than the less-affected side. Previous studies have reported that people with PD exhibit laterality in muscle strength, abnormal MU firing behavior, and degeneration of the central nervous system [ 11 , 26 ]. These previous findings are in accordance with the results of this study showing that compared with the less-affected side, the more-affected side exhibited less muscle strength, larger abnormalities in MU firing behavior, and more severe degeneration of the central lesion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The more-affected side showed a lower knee extensor torque, recruitment threshold, and SBR Bolt , and a higher CV of the mean MU firing rate than the less-affected side. Previous studies have reported that people with PD exhibit laterality in muscle strength, abnormal MU firing behavior, and degeneration of the central nervous system [ 11 , 26 ]. These previous findings are in accordance with the results of this study showing that compared with the less-affected side, the more-affected side exhibited less muscle strength, larger abnormalities in MU firing behavior, and more severe degeneration of the central lesion.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that people with PD showed a possible shift in the MU population to a lower recruitment threshold than healthy control subjects. Furthermore, our previous report showed that there was a significant correlation between the mean MU firing rate and recruitment threshold on the less-affected side but not on the more-affected side [ 11 ]. MU firing behavior is primarily determined by the excitatory input of synapses from the corticospinal tract to the motor neuron pool [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations